2015
DOI: 10.1093/jmammal/gyu008
|View full text |Cite
|
Sign up to set email alerts
|

Validating the use of trap-collected feces for studying the gut microbiota of a small mammal (Neotoma lepida)

Abstract: Gut microbes can largely influence the ecology and evolution of mammalian hosts. As research in this area increases, it will be necessary to collect fecal samples from nature to inventory microbial populations. Here, we tested the appropriateness of using feces collected from live-traps for microbiome studies. We found that feces collected from the traps containing the desert woodrat (Neotoma lepida) did not differ from aseptically collected feces in terms of microbial community structure, abundances of bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 20 publications
3
12
0
Order By: Relevance
“…To address this concern, we collected fecal samples from woodrats in the wild and over a time series in captivity. We confirmed that feces collected from traps in nature were representative of aseptically collected samples ( Kohl et al, 2015 ). Woodrats retained a majority (>60%) of their natural gut microbes, even after 6 months in captivity ( Kohl and Dearing, 2014 ).…”
Section: Woodrats As a Tractable System For Gut Microbial Ecologysupporting
confidence: 71%
“…To address this concern, we collected fecal samples from woodrats in the wild and over a time series in captivity. We confirmed that feces collected from traps in nature were representative of aseptically collected samples ( Kohl et al, 2015 ). Woodrats retained a majority (>60%) of their natural gut microbes, even after 6 months in captivity ( Kohl and Dearing, 2014 ).…”
Section: Woodrats As a Tractable System For Gut Microbial Ecologysupporting
confidence: 71%
“…However, this study only used a single pooled faecal sample and so it is unclear whether the effects of time are larger or smaller than variation across individuals. Another controlled study with multiple individuals of wood rats found that individual microbial signatures were highly retained between fresh faeces and those collected from the floor of Sherman traps after the rodent hosts spent a night in the trap with cotton batting, apple slices and oatmeal bait for~10 h (Kohl et al 2015). Thus, further investigations into the different types of microbial samples and sources of variation are needed.…”
Section: Discussionmentioning
confidence: 99%
“…However, this study used a single pooled faecal sample, and so it is unclear whether the effects of time are larger or smaller than inter‐individual variation. A controlled study with multiple individuals of woodrats found that individual microbial signatures were highly retained between fresh faeces and those collected from the floor of Sherman traps after the rodent hosts spent a night in the trap with cotton batting, apple slices and oatmeal bait for ~10 hr (Kohl, Luong, & Dearing, ). Thus, it is unlikely that the effects of field conditions are solely responsible for the large differences in microbial community structure across populations.…”
Section: Discussionmentioning
confidence: 99%